PENGARUH VARIETAS KELAPA SAWIT TERHADAP KOMPONEN LEMAK DAN KANDUNGAN BIOAKTIF PADA PRODUK MINYAK OLEIN MERAH - Donald Siahaan; Giyanto Giyanto; Qori Bernike Tarigan (Institut Teknologi Sawit Indonesia, 2018)
Derived products from the processing of fresh fruit bunches that contain high nutrients is red olein palm oil. Nutrients in raw materials can be aﬀected by crop varieties. This study aimed to compare the characteristics of triglyceride composition and the level of bioactive components of red palm oil. The research was conducted on 3 crosses namely DxP Langkat, DxP Yangambi and DxP PPKS 718. This research was conducted at PPKS Laboratory Medan in March-August 2017. Based on the research that has been done can be concluded that: The level of palmitic acid is in the range of 38-41%, 41-43% oleic acid with the position of saturated and unsaturated fatty acids in red palm oil from DxP Langkat crosses. Triglyceride composition of 3 crosses has no significant eﬀect. Highest vitamin E levels found in red palm oil from DxP Langkat. Total β carotene levels include very high and normal squalen levels.